1996
DOI: 10.1021/jf950152r
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Chicken Breast Muscle Proteins in Solutions of Low Ionic Strength

Abstract: Essentially all of the proteins of chicken breast muscle were soluble in sodium chloride solutions of physiological ionic strength or less and neutral pH. However, there was a critical order of treatment necessary to accomplish this. After removal of those proteins solubilized by homogenizing the tissue 1:10 (w/v) in water, it was necessary to solubilize a fraction of the remaining proteins in moderate concentrations (25-150 mM) of sodium chloride at neutral pH before the remaining proteins could be solubilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 18 publications
(32 reference statements)
1
33
0
Order By: Relevance
“…Takai et al (2013) showed that the marginal solubilisation effect of lys might be because of the strong tendency of myosin to self-associate into filaments at low NaCl concentration, and a specific interaction between lys and myosin may disrupt the electrostatic interactions and prevent filament formation. Krishnamurthy et al (1996) suggested that L-his was important for neutralising the low ionic strength solution and did not have a specific effect on the solubilisation of myofibrillar proteins. Contrary to the Krishnamurthy et al (1996) study, Hayakawa et al (2009 found that L-his directly affected the solubility of myosin in a low (1 mM) ionic strength solution rather than observing a pH effect.…”
Section: Solubility Of Porcine Myosin Solutionmentioning
confidence: 99%
See 3 more Smart Citations
“…Takai et al (2013) showed that the marginal solubilisation effect of lys might be because of the strong tendency of myosin to self-associate into filaments at low NaCl concentration, and a specific interaction between lys and myosin may disrupt the electrostatic interactions and prevent filament formation. Krishnamurthy et al (1996) suggested that L-his was important for neutralising the low ionic strength solution and did not have a specific effect on the solubilisation of myofibrillar proteins. Contrary to the Krishnamurthy et al (1996) study, Hayakawa et al (2009 found that L-his directly affected the solubility of myosin in a low (1 mM) ionic strength solution rather than observing a pH effect.…”
Section: Solubility Of Porcine Myosin Solutionmentioning
confidence: 99%
“…Krishnamurthy et al (1996) suggested that L-his was important for neutralising the low ionic strength solution and did not have a specific effect on the solubilisation of myofibrillar proteins. Contrary to the Krishnamurthy et al (1996) study, Hayakawa et al (2009 found that L-his directly affected the solubility of myosin in a low (1 mM) ionic strength solution rather than observing a pH effect. Further studies showed that possible reason for this was because of elongation of LMM region, contributing to myosin filament weakening and the dissociation of myosin in a low ionic strength solution (Hayakawa et al, 2010).…”
Section: Solubility Of Porcine Myosin Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Krishnamurthy et al. () reported CaCl 2 solutions of low ionic strength provided and inhibitory effect of protein solubility. However, as ionic strength increased, protein solubility returned to levels similar to what was observed in NaCl solutions (Krishnamurthy et al., ).…”
Section: Resultsmentioning
confidence: 99%